Comparison of outcomes after laparoscopy‐assisted and open total gastrectomy for early gastric cancer. Issue 12 (23rd September 2015) - Lee, J. H.; Nam, B.‐H.; Ryu, K. W.; Ryu, S. Y.; Park, Y. K.; Kim, S.; Kim, Y. W.
<x xml:space="preserve">Abstract</x> Background The aim of this study was to compare the results of laparoscopy‐assisted total gastrectomy with those of open total gastrectomy for early gastric cancer. Methods Patients with gastric cancer who underwent total gastrectomy with curative intent in three Korean tertiary hospitals between January 2003 and December 2010 were included in this multicentre, retrospective, propensity score‐matched cohort study. Cox proportional hazards regression models were used to evaluate the association between operation method and survival. Results A total of 753 patients with early gastric cancer were included in the study. There were no significant differences in the matched cohort for overall survival (hazard ratio (HR) for laparoscopy‐assisted versus open total gastrectomy 0·96, 95 per cent c.i. 0·57 to 1·65) or recurrence‐free survival (HR 2·20, 0·51 to 9·52). The patterns of recurrence were no different between the two groups. The severity of complications, according to the Clavien–Dindo classification, was similar in both groups. The most common complications were anastomosis‐related in the laparoscopy‐assisted group (8·0 per cent versus 4·2 per cent in the open group; P = 0·015) and wound‐related in the open group (1·6 versus 5·6 per cent respectively; P = 0·003). Postoperative death was more common in the laparoscopy‐assisted group (1·6 versus 0·2 per cent; P = 0·045). Conclusion Laparoscopy‐assisted total gastrectomy for early gastric cancer is feasible in terms of long‐term results, including survival and recurrence. However, a higher postoperative mortality rate and an increased risk of anastomotic leakage after laparoscopic‐assisted total gastrectomy are of concern.